Bulletproof web services follow basic principles. - Kolawa, Dr. Adam (SOA webservices journal.)
Web services are gaining industry wide acceptance and usage. They are moving from proof of concept deployments to actual usage in mission critical enterprise applications. While Web services allow businesses to connect to partners and customers, the same flexibility and connectivity provide an increased opportunity for errors.